The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.4049/jimmunol.177.3.1516
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Expansion and Contraction of CD8+ T Cell Response during Infection with VirulentSalmonella typhimurium

Abstract: Ag presentation to CD8+ T cells often commences immediately after infection, which facilitates their rapid expansion and control of infection. Subsequently, the primed cells undergo rapid contraction. We report that this paradigm is not followed during infection with virulent Salmonella enterica, serovar Typhimurium (ST), an intracellular bacterium that replicates within phagosomes of infected cells. Although susceptible mice die rapidly (∼7 days), resistant mice (129×1SvJ) harbor a chronic infection lasting ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 69 publications
2
73
1
Order By: Relevance
“…It is also a highly virulent organism which devotes Ͼ4% of its genome to virulence mechanisms (56). Thus, even in the fully competent host, adaptive immunity to Salmonella is substantially delayed (8), making it important for innate immunity to control infection. Consequently, even a slightly deviated and/or delayed cytokine/cellular innate response during pregnancy may lead to catastrophic host outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also a highly virulent organism which devotes Ͼ4% of its genome to virulence mechanisms (56). Thus, even in the fully competent host, adaptive immunity to Salmonella is substantially delayed (8), making it important for innate immunity to control infection. Consequently, even a slightly deviated and/or delayed cytokine/cellular innate response during pregnancy may lead to catastrophic host outcome.…”
Section: Discussionmentioning
confidence: 99%
“…ϩ T cell response to ST infection is generally detectable only beyond 7 days of infection (7), whereas CD8 ϩ T cell response is substantially delayed until the second week postinfection (8). Overall, ST appears to have evolved many mechanisms to evade the host immune system and establish chronic infection.…”
mentioning
confidence: 99%
“…), and parasitic (Toxoplasma gondii and Trypanosoma cruzi) infections, there is a delay in the generation of the CD8 + T cell immune response. In addition, Ag-specific T cells become dysfunctional, express inhibitory receptors, and even fail to control the infection (57)(58)(59)(60)(61)(62)(63)(64). Although this process was initially described for models of chronic viral infections, such as lymphocytic choriomeningitis, HIV, simian immunodeficiency, and HBV and HCV (12), recent studies have shown that this phenomenon also occurs in protozoan infections (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…19,26 27 and were maintained on a CD45.1 + Rag-1-deficient background. For adoptive transfer, 5 · 10 4 CD4 + T cells from SM1 TCR transgenic mice or 1 · 10 7 to 2 · 10 7 CD4 + T cells from CD45.1 + T cells were intravenously transferred 1 day before infection.…”
Section: Micementioning
confidence: 99%